Research and Development of Location-Based Services for an Educational Environment - Tvaranavicius, Paulius (2016)
Location-based services (LBS) provide a way to personalize the information and interactions for users on mobile devices. Knowing the location of the device being used creates opportunities to improve the already existing services and to create new ones that could not exist without such capability. The purpose of this research was to identify what LBS might be useful in a large university. An interview with university’s user experience team, a review of other LBS applications and a focus group with students generated a list of services which students would like to see in a university’s mobile application focused on LBS. An interactive prototype was developed to evaluate the services and to identify what features they should have. In the process of prototyping and evaluating more services were added. The study suggests that students show interest in location based services. They would like to get reminders for lectures on their mobile devices based on their location, see live bus information, check the occupancy of various places around the campus, etc.